2002
DOI: 10.1039/b110084j
|View full text |Cite
|
Sign up to set email alerts
|

LIF study of the reactions of the IO radical with NO and NO2 over an extended range of temperature and pressure

Abstract: A pulsed laser-photolysis / pulsed laser induced fluorescence technique was used to investigate the kinetics of the reactions of the IO radical with NO and NO 2 . For the reaction (1) IO + NO ! I + NO 2 the rate constants between 233 and 346 K were found to be k IO+NO (T) ¼ (4.3 AE 1.0) Â 10 À12 exp[(397 AE 65) K/T] cm 3 s À1 , independent of pressure between 13 and 130 mbar as measured at 286 K. Reaction (2) IO + NO 2 + M ! IONO 2 + M has been studied between 48 and 402 mbar in the temperature range 238-298 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Until recently, CH 3 I was thought to be the main natural source of gaseous organic iodine accounting for more than 90% of the atmospheric organic iodine budget. Mostly emitted from the ocean, field observations suggest CH 3 I average mixing ratios are 0.4–4 pptv 2–8 although mixing ratios as high as 43 pptv 3 have been reported in coastal sites associated with high biological activity. Atmospheric sources of CH 3 I include marine phytoplankton 9, biomass, and fossil fuel burning and chemical industry 10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, CH 3 I was thought to be the main natural source of gaseous organic iodine accounting for more than 90% of the atmospheric organic iodine budget. Mostly emitted from the ocean, field observations suggest CH 3 I average mixing ratios are 0.4–4 pptv 2–8 although mixing ratios as high as 43 pptv 3 have been reported in coastal sites associated with high biological activity. Atmospheric sources of CH 3 I include marine phytoplankton 9, biomass, and fossil fuel burning and chemical industry 10.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, CH 3 I was thought to be the main natural source of gaseous organic iodine accounting for more than 90% of the atmospheric organic iodine budget. Mostly emitted from the ocean, field observations suggest CH 3 I average mixing ratios are 0.4-4 pptv [2][3][4][5][6][7][8] Correspondence to: Rafal. S. Strekowski; e-mail: rafal .strekowski@univ-provence.fr.…”
Section: Introductionmentioning
confidence: 99%
“…3 The coupling of iodine oxides with other radical families is critical as such processes lead to destruction of the ozone layer. The reactions of IO, in particular with itself, ClO, BrO and HO 2 have been examined in detail and have been shown to be important processes affecting the concentrations of ozone in the lower atmosphere, 2,[4][5][6][7] which would lead to the following ozone depletion cycles: …”
Section: Introductionmentioning
confidence: 99%
“…In the 1980s, Class et al and Barrie et al reported the contribution of bromine atoms to the ozone destruction, and Chameides and Davis proposed that the iodine contribution could be even more important. Thereafter, there have been several studies on the photochemical reactions of iodomethanes and their impacts on the ozone layer. Saiz-Lopez et al recently summarized the atmospheric chemistry of iodine and concluded that the atmospheric iodine atoms are mostly generated from the photolysis of iodomethanes such CH 2 I 2 , CH 3 I, CH 2 ICl, and CH 2 IBr.…”
Section: Introductionmentioning
confidence: 99%